Middle Assyrian seal motifs from Tell Fekheriye (Syria) - Bonatz, Dominik (Tell Fekheriye excavation reports, 2021)
The series is dedicated to the ancient site of Tell Fekheriye in Syria which is believed to have played a central role in the political and cultural history of the region during mainly the Late Bronze Age and later the Roman-Byzantine periods. In fact, the excavations exposed impressive architectural remains and finds from the period when the site was under the hegemony of first the Mittani and then the Middle Assyrian state (ca. 1500-1100 BC).